Short-term feeding of MGA to postpartum cows prior to the breeding season - J.F. Gleghorn; T.T. Marston; L.E. Wankel (Kansas Agricultural Experiment Station Research Reports, 2001)
A protocol to make anestrous cows more likely to cycle prior to estrous synchronization would greatly enhance reproductive efficiency. Ease of application, availability, and low cost make feeding melengestrol acetate (MGA) a good choice in such a protocol. MGA, used as a progestin "primer," has no detrimental effects on cows that are already cycling and reduces the number of cows expressing short cycles.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; MGA; Postpartum interval; Pregnancy rate; Short cycle